2011
DOI: 10.1037/a0021126
|View full text |Cite
|
Sign up to set email alerts
|

The automatic aesthetic evaluation of different art and architectural styles.

Abstract: The subject under discussion concerns the existence of an automatic aesthetic evaluation. When we encounter an object like an artwork or an architectural structure that activates an aesthetic response, does the associated evaluation appear in our mind as an automatic process? From the broad field of aesthetic appraisal, we will be considering a specific aspect that refers only to the positive and negative affects related to an individual's preference between two art styles (figurative vs. abstract) and two arc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 45 publications
6
56
1
1
Order By: Relevance
“…Psychophysiological indicators can be considered implicit measures of the individual reaction to art stimuli. Previous studies have shown differences in the implicit evaluation of different art, architecture and design styles; classical stimuli were more appreciated than modern ones, but not in an explicit evaluation (Mastandrea, Bartoli, & Carrus, 2011;Mastandrea & Maricchiolo, 2014).…”
Section: Art Museums As Restorative Environmentsmentioning
confidence: 95%
“…Psychophysiological indicators can be considered implicit measures of the individual reaction to art stimuli. Previous studies have shown differences in the implicit evaluation of different art, architecture and design styles; classical stimuli were more appreciated than modern ones, but not in an explicit evaluation (Mastandrea, Bartoli, & Carrus, 2011;Mastandrea & Maricchiolo, 2014).…”
Section: Art Museums As Restorative Environmentsmentioning
confidence: 95%
“…In the current work, we test correspondence theory using the Implicit Association Test (IAT, Greenwald et al, 1998; Nosek et al, 2007), which has been used in thousands of experiments, often revealing associations between dimensions which people are either explicitly unaware of, or even explicitly reject. Recently, the IAT has been used to answer various questions in empirical aesthetics (Gattol et al, 2011; Mastandrea et al, 2011; Makin et al, 2012a,b; Bertamini et al, 2013b). Importantly, the IAT procedure requires participants to classify all stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Implicit preference, on the other hand, was consistent with the speed of visual processing, with consistent preferences for the more rapidly Implicit association of symmetry with positive valence, high arousal and simplicity detected patterns. It is clear that the IAT is a useful tool in experimental aesthetics (Gattol, Sääksjärvi, & Carbon, 2011;Makin, Pecchinenda, & Bertamini, 2012b;Mastandrea et al, 2011). For instance, Pavlović and Marković (2012) found that positive paintings were paired with positive words and hedonically negative ones with negative words.…”
Section: Introductionmentioning
confidence: 99%
“…Makin, Pecchinenda, and Bertamini (2012a) used the Implicit Association Test (IAT; Greenwald, McGhee, & Schwartz, 1998;Nosek, Greenwald, & Banaji, 2007) to explore implicit preference for symmetry. Other authors have used the IAT for buildings (Mastandrea, Bartoli, & Carrus, 2011) or for paintings (Pavlović & Marković, 2012). This technique is designed to detect the strength of a person's automatic association between two categories.…”
Section: Introductionmentioning
confidence: 99%